ANALYSIS OF CESAREAN SECTIONS USING ROBSON’S 10 GROUP CLASSIFICATION: NEED OF THE HOUR - ROHIT SHANTILAL DIMBAR; MANGAL SANTOSH SUPE; SMITA MAROTIRAO THAKKARWAD (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The number of women delivering by cesarean sections has increased exponentially over the past decade hence making its reanalysis of absolute importance. Delving into the indications and rationale of this surgery is crucial. An audit of the cesarean sections performed in a Post- Graduate teaching institute with the use of Robson’s classification. Methods: A retrospective study was carried out for 4 years in PGI YCMH, Pimpri from January 2018 to December 2021, where details of women delivered by the cesarean section were collected. The indications for cesarean section were sorted as stated by Robson’s classification and the results were analyzed. Results: The cesarean section rate in the hospital during the study duration was 35.22%. The highest contribution to the study population was from group 2 (23.4%) and then from group 1 (18.1%) and 3 (17.5%). The lowest representations were from groups 9 (0.43%) and 8 (1.01%). Group 5 had the greatest contribution to the total cesarean section rate (44.57%) closely followed by group 2 (19.98). Group 9 had a 100% cesarean section rate even though it was only 0.43% of the population. Conclusion: An audit of the cesarean section as an important intervention is needed and Robson’s classification should be utilized in all maternity care. This will help in triaging the indications, give insights into important indications, and provide a glimpse of the burden of the intervention. This will help us to reduce unwanted cesarean sections. Robson’s classification can be of great help in it; however, it has some limitations which need to be looked at.